2007
DOI: 10.1080/07399330701226453
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Suicidal Ideation Within a Sheltered Sample of Raped and Battered Women

Abstract: The relationship between suicide attempts and the experience of intimate partner physical violence has been examined in recent literature. The present study extended this literature by examining the relationship between intimate partner rape and suicidal ideation in a sheltered sample of battered women. Fifty women were recruited from a regional shelter setting for battered women in a Midwestern city in the United States. Fifty-eight percent had experienced intimate partner rape. More than one-third of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Eighty-one percent of the women with mild chronic pain and 92% of the women with moderate to severe chronic pain met the diagnosis of PTSD (Foa et al, 1993). These findings are similar to previous studies using the same measure with sheltered battered women samples (Phillips, Rosen, Zoellner, & Feeny, 2006;Weaver et al, 2007;Woods, Wineman, et al, 2005) but higher than a sample recruited from midwestern hospitals and clinics (Perez & Johnson, 2008). Nevertheless, these findings document the persistence of PTSD even in community-based formerly abused women.…”
Section: Discussionsupporting
confidence: 88%
“…Eighty-one percent of the women with mild chronic pain and 92% of the women with moderate to severe chronic pain met the diagnosis of PTSD (Foa et al, 1993). These findings are similar to previous studies using the same measure with sheltered battered women samples (Phillips, Rosen, Zoellner, & Feeny, 2006;Weaver et al, 2007;Woods, Wineman, et al, 2005) but higher than a sample recruited from midwestern hospitals and clinics (Perez & Johnson, 2008). Nevertheless, these findings document the persistence of PTSD even in community-based formerly abused women.…”
Section: Discussionsupporting
confidence: 88%
“…This may be reflected in research that has found interpersonal problems to be a significant predictor of depressive psychopathology in transgender adults and that self-esteem significantly mediates the association between interpersonal problems and low quality of life (Bouman, Davey, Meyer, Witcomb, & Arcelus, 2016). Among women who experienced physical violence, depression significantly mediated the relationship of intimate partner violence and suicidal ideation (Weaver et al, 2007). These findings suggest the important role of self-worth in predicting well-being and in particular suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of childhood and adult sexual violence suffer from a variety of mental health problems and destructive high-risk sexual behaviors. Some of the most common mental health conditions that are experienced by victims of sexual abuse include posttraumatic stress disorder; low selfesteem; depression; anxiety disorders; eating disorders; alcohol and substance abuse; self-mutilation (cutting or burning oneself); suicidal ideation and=or attempts (Ullman, 2004;Weaver et al, 2007); mental illness (dissociative problems); and an extreme fear and distrust of others, especially men (Girshick, 2003;Hall, 2000;Mullings, Hartley, & Marquart, 2004). Childhood sexual trauma has also been linked to other personality disorders, including those that are distinguished by patterns of distrust and paranoia (Yuan, Koss, & Stone, 2006).…”
Section: Trauma and Victimization Manifestationsmentioning
confidence: 99%